2013
DOI: 10.2147/ijgm.s45825
|View full text |Cite
|
Sign up to set email alerts
|

Lymphangiopathy in neurofibromatosis 1 manifesting with chylothorax, pericardial effusion, and leg edema

Abstract: BackgroundThis case report documents the affliction of the lymph vessels as a phenotypic feature of neurofibromatosis-1 (NF-1).MethodologyRoutine transthoracic echocardiography, computed tomography scan of the thorax, magnetic resonance angiography of the renal arteries, and conventional digital subtraction angiography were applied. Comprehensive NF-1 mutation analysis was carried out by fluorescence in situ hybridization analysis, long-range reverse transcriptase polymerase chain reaction, and multiple-ligati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…There are reports of vascular malformations, mainly lymphatic, associated with recurrent pericardial effusion, but none of the pathologies included in the PUVA or treated with sirolimus. [14][15][16] However, the characteristics of the vascular anomaly described above make this a unique malformation, and we have not found similar reports to date. Probably in the coming years, as our knowledge of patho-genic and signaling pathways advances, we will be able to give a more precise name or classification to many of the entities we now call PUVA, since the genes that cause some of these disorders are known, but we do not know most of their mechanisms.…”
Section: Discussionmentioning
confidence: 70%
“…There are reports of vascular malformations, mainly lymphatic, associated with recurrent pericardial effusion, but none of the pathologies included in the PUVA or treated with sirolimus. [14][15][16] However, the characteristics of the vascular anomaly described above make this a unique malformation, and we have not found similar reports to date. Probably in the coming years, as our knowledge of patho-genic and signaling pathways advances, we will be able to give a more precise name or classification to many of the entities we now call PUVA, since the genes that cause some of these disorders are known, but we do not know most of their mechanisms.…”
Section: Discussionmentioning
confidence: 70%
“…Lifestyle illnesses such as hypertension, stroke, and heart disease are also common [ 1 ]. Localized overgrowth of bone and soft-tissue gives an elephantiasis-like appearance [ 3 ], which is also attributed to lymphadenopathies presenting as edema [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the specific type of gene mutation in RASopathy with MAT in our study corresponds well to the report of Lin et al 18) However, since MAT and/or atrial tachycardia have recently been reported in neurofibromatosis or Noonan syndrome with mutations other than RAF1, MAT may not be a differential feature distinguishing Costello syndrome from other RASopathies. 19) 20) …”
Section: Discussionmentioning
confidence: 99%